Ethical and Legal Aspects of Breast Cancer Prevention in Individuals Living with Mental Disabilities: Legally Incapacitated - Hojjat Torkmandi; karim torabi; mohammad abdi; Sanaz Homayoon (Shiraz University of Medical Sciences, 2022)
Ethics and law studies examine several issues in the field of medicine, one of which is the legal aspects related to patients living with mental disability. In a previous article, we introduced a 24-year-old female patient living with mental disability, diagnosed with large tumor growth in her right breast. Inadequate self-care as well as lack of breast self-examination were the causes of delayed referral and late diagnosis. The patient's family stated that no periodic breast examination was performed by the family or health centers. The patient's family did not have sufficient knowledge about caring for patients with mental disabilities. The question that will then arise under such circumstances is, will the legal system protect the incapacitated individuals if they or their family cannot provide for themselves? In this article, we discuss this issue and the existing legal vacuum.